2023
DOI: 10.1186/s12879-023-08224-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting norovirus and rotavirus resurgence in the United States following the COVID-19 pandemic: a mathematical modelling study

Abstract: Background To reduce the burden from the COVID-19 pandemic in the United States, federal and state local governments implemented restrictions such as limitations on gatherings, restaurant dining, and travel, and recommended non-pharmaceutical interventions including physical distancing, mask-wearing, surface disinfection, and increased hand hygiene. Resulting behavioral changes impacted other infectious diseases including enteropathogens such as norovirus and rotavirus, which had fairly regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In many countries, the restrictions were relaxed and raised concerns about a potential rapid rise in infectious diseases, including RVA. Mathematical modeling studies suggest that, if contact patterns return to pre-pandemic levels, the population’s susceptibility to RVA and norovirus infections would likely increase [ 46 , 47 ]. During our study, the RVA detection rate decreased dramatically in 2021 (0.5%) to a rate that was significantly lower than the rates observed in previous years in Brazil [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, the restrictions were relaxed and raised concerns about a potential rapid rise in infectious diseases, including RVA. Mathematical modeling studies suggest that, if contact patterns return to pre-pandemic levels, the population’s susceptibility to RVA and norovirus infections would likely increase [ 46 , 47 ]. During our study, the RVA detection rate decreased dramatically in 2021 (0.5%) to a rate that was significantly lower than the rates observed in previous years in Brazil [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This shift is considered to have been due to travel, social restrictions, and non-pharmaceutical interventions ( Dapper et al, 2022 ). After resuming social activities, RVA strains are speculated to once again readily spread domestically and internationally, as noted in other articles ( Lappe et al, 2023 ; Wang et al, 2023 ). Continuous molecular epidemiological studies based on full genome analysis will continue to be critical for detecting the emergence of new epidemic RVA strains.…”
Section: Discussionmentioning
confidence: 67%
“…In the same line, a study in Shanghai, China, showed that the detection rate of norovirus among children ≤5 years of age with AGE symptoms abruptly decreased in 2020, the first year of the COVID-19 pandemic, compared to 2021 and 2022 [27]. Mathematical modeling studies have suggested that, if contact patterns return to pre-pandemic levels, the population's susceptibility to rotavirus and norovirus infections would likely increase [52,53].…”
Section: Discussionmentioning
confidence: 96%